Resource Taxes in Russia and China: Pro et Contra - Evgenia Anatolievna Kuklina (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article discusses the resource potential in the context of national security. The authors describe ‘traps’ of a resource economy. There are assessed the role and importance of natural resource taxation in Russia and China. The dynamics of tax income from mineral resources is given. There are substantiated the main directions of improving taxes and payments for mineral in Russia and China.